2019
DOI: 10.1088/1361-6560/ab142e
|View full text |Cite
|
Sign up to set email alerts
|

Predicting VMAT patient-specific QA results using a support vector classifier trained on treatment plan characteristics and linac QC metrics

Abstract: The use of treatment plan characteristics to predict patient-specific quality assurance (QA) measurement results has recently been reported as a strategy to help facilitate automated pre-treatment verification workflows or to provide a virtual assessment of delivery quality. The goal of this work is to investigate the potential of using treatment plan characteristics and linac performance metrics (i.e. quality control test results) in combination with machine learning techniques to predict the results of VMAT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
97
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(100 citation statements)
references
References 31 publications
2
97
0
1
Order By: Relevance
“…Recently El Naqa et al used machine learning methods based on support vector data description to detect anomalies in treatment machine performance using EPID . Granville et al used a linear support vector classifier that includes both treatment plan complexity and linac performance metrics to predict VMAT patient QA results measured using a diode array . Deep learning approaches based on convolution neural networks without the extraction of the plan complexity metrics have been reported to predict patient‐specific QA results and could achieve comparable prediction performance as machine learning approaches .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently El Naqa et al used machine learning methods based on support vector data description to detect anomalies in treatment machine performance using EPID . Granville et al used a linear support vector classifier that includes both treatment plan complexity and linac performance metrics to predict VMAT patient QA results measured using a diode array . Deep learning approaches based on convolution neural networks without the extraction of the plan complexity metrics have been reported to predict patient‐specific QA results and could achieve comparable prediction performance as machine learning approaches .…”
Section: Discussionmentioning
confidence: 99%
“…39 Granville et al used a linear support vector classifier that includes both treatment plan complexity and linac performance metrics to predict VMAT patient QA results measured using a diode array. 18 Deep learning approaches based on convolution neural networks without the extraction of the plan complexity metrics have been reported to predict patient-specific QA results and could achieve comparable prediction performance as machine learning approaches. 14,16,17 In this study, we have demonstrated that portal dosimetry gamma passing rates can be accurately predicted using tree-based machine learning models.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ML models were also used in predicting the patient-specific IMRT/VMAT QA, by predicting the gamma passing rate. [19][20][21][22][23][24][25][26] Some recently published studies [19][20][21][22][23][24][25][26] investigated the feasibility of Poisson regression with LASSO regularization, [19][20][21] deep learning based on convolutional neural networks (CNN), [22][23][24] ensemble learning based on decision-tree, 25 random forest, 21 and support vector machine 26 ML models. All these proposed ML-based models demonstrated a capability in accurately predicting the IMRT/ VMAT QA gamma passing rates.…”
Section: Introductionmentioning
confidence: 99%